POST-JUNCTIONAL ALPHA ADRENOCEPTORS IN THE ANOCOCCYGEUS MUSCLE AND VAS DEFERENS: A COMPARATIVE STUDY IN NORMOTENSIVE AND SPONTANEOUSLY HYPERTENSIVE RATS (1984)
The characteristics of the post-junctional α-adrenoceptors in the isolated anococcygeus muscle and vas deferens were compared in spontaneously hypertensive rats (SHR) and normotensive rats (NCR). Responses to α —adrenoceptor agonists were obtained in the absence and presence of cocaine and of antagonists. Noradrenaline (NA) and phenylephrine (PE) produced concentration related contrations of the preparations which were antagonised by phentolamine, prazosin and yohimbine in both rat strains, indicating α -adrenoceptor mediation. The effects of cocaine revealed the relative efficiency of the uptake mechanism in each preparation. In the anococcygeus NA was equipotent in the NCR and SHR in the absence of cocaine whereas it was less potent in the SHR in the presence of cocaine, PE was less potent in the SHR in the absence and presence of cocaine. Antagonism was assessed by pA2 and K(diss) determinations. Potencies were compared only when antagonism was competitive in both strains. In the anococcygeus low concentrations of prazosin (L-Praz) non—competitively antagonised NA but antagonised PE equally and competitively in both strains. Higher concentrations (H-Praz) competitively antagonised NA in both strains. Phentolamine was competitive against NA in NCR and against PE in both strains. However, it was non-competitive against NA in SHR, Low concentrations of yohimbine (L—YOH) competitively antagonised NA and PE in both the NCR and SHR but the K(diss) values were significantly different. Higher concentrations (H—YOH) was competitive against NA in the NCR and PE in both strains. In the vas L-Praz competitively antagonised both NA and PE in the NCR but gave non—competitive antagonism of both strains in the SHR, Phentolamine antagonised NA competitively in the NCR but non-competitively in the SHR. It was equipotent and competitive against PE in both strains. L—YOH non-competitively antagonised NA and PE in the NCR but in the SHR it was competitive. H-YOH antagonism was non—competitive against both NA and PE in both strains. It is suggested that there might be both the α1— and α2 post—junctional adrenoceptor in the NCR anococcygeus muscle, Prazosin and yohimbine seem to be able to differentiate between the two receptor subtypes at low concentrations, It is suggested further that the α2- subpopulation might not possess identical characteristics in the NCR and SHR anococcygeus. Also, there might be an alteration in NA uptake properties in the SHR, In the NCR vas deferens there seems to be a predominance of post-junctional α1-adrenoceptors. In the SHR vas, there might be an increase in the post-junctional α-adrenoceptor population and/or sensitivity. Furthermore, it seems that the post—junctional α2-adrenoceptor characteristics are somewhat different in the SHR, Uptake1 is suggested to be less efficient in the SHR vas.